Dancing with the D-man: Exploring reflexive practices of relational leadership in ballet and ice hockey. (December 2019) - Ryömä, Arto; Satama, Suvi
This paper explores relational leadership as a reflexive activity that comprises the subtle interplay between the verbal and bodily acts of people at work. Although the existing literature on collective leadership acknowledges various qualities of relational leadership, the latter's deeply reflexive nature has remained underexplored. By drawing on ethnographic research material from the two controversial; yet, surprisingly similar contexts of ballet and ice hockey, we set out to explore the fine-grained dynamics of the reflexive practices of relational leadership in greater detail. Based on our findings, we argue that relational leadership builds on a bundle of verbal and embodied reflexive practices, entwined with offstage and onstage power dynamics in the workplace. Consequently, our study calls for a more nuanced and bodily appreciative understanding of relational leadership in organisation studies in general.